Analisis Usability Sistem Permohonan Legalisir Menggunakan Metode System Usability Scale - Wahyudi Ariannor; Devia Rahma Safitri; Rustati Rahmi (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
One of the applications of e-Government in the districts is the application for legalization of documents that can be accessed widely. Since it was implemented, the application has never been evaluated for usability. So that the ease of use of the application can not be determined. The study measures the usability of quantitative applications using the System Usability Scale (SUS) method using a 10-item rating scale. Based on the test results, the usability value of general public application users has a "Good" value for an adjective rating and has a "D" scale for a grade scale. Meanwhile, the acceptability ranges are at a "High-Marginal" value. Then the usability value of the agency user gets the value "Good" for the adjective rating and has a "C" scale for the grade scale. The acceptability ranges are at a "High-Marginal" value. Aspects that are important to note for improvement or further application development are the aspects of errors and aspects of satisfaction.Keyword: Analisys; Satisfaction; Errors; User experience AbstrakSalah satu penerapan e-Goverment di kantor kecamatan adalah aplikasi permohonan legalisir dokumen yang dapat diakses secara luas. Sejak diimplementasikan, aplikasi belum pernah dilakukan evaluasi usability. Sehingga belum dapat dipastikan kemudahan penggunaan aplikasi oleh pengguna. Penelitian mengukur usability terhadap aplikasi kuantitatif menggunakan metode System Usability Scale (SUS) menggunakan 10 item skala penilaian. Berdasarkan hasil pengujian, nilai usability pengguna aplikasi masyarakat umum memiliki nilai Good untuk adjective rating dan memiliki skala “D” untuk grade scale. Sedangkan pada acceptability ranges berada pada nilai High-Marginal. Kemudian nilai usability pengguna instansi didapatkan nilai Good untuk adjective rating dan memiliki skala “C” untuk grade scale. Pada acceptability ranges berada pada nilai High-Marginal. Aspek yang penting untuk diperhatikan untuk perbaikan atau pengembangan aplikasi lebih lanjut adalah aspek errors dan aspek satisfaction.